ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PEMESANAN PLYWOOD BERBASISKAN WEB PADA PT. KUMPEH KARYA LESTARI JAMBI - Leni Kardila Deti; Herry Mulyono (Jurnal Manajemen Sistem Informasi, 2017)
Kumpeh Karya Lestari Jambi company is an enterprise which moves in selling venneer standart materialin doing the marketing and selling process using manual way. It means from person to person or from onecompany to another company. In the beginning, this company only produces the product to be sold tolocal area or only in jambi. To enlarge in selling the the product, the writer try to make on line sellingapplication or based on web. Through this aplication, the subscriber can buy the product whithour sellingthe seller face by face the transaction whichis done using website should give the ease to many peopleand the subscriber in having an access to do this, use programming language MySQL and PHP (HipertextPrepocessor). The result from using website in selling is hoped to be able to give the ease in doing theinformation quickly accurately and properly, and also give the ease and security to the subcriber in doingtransaction.